Code Switching and Code Mixing in Arabic Conversations Among Female Students at the Walisongo Cukir Jombang Islamic Boarding School (Sociolinguistic Studies)/ Takhlitu as-Syafarah wa TahwÎluha fi al-Muhâdtsah al-Arabiyah ‘inda Thâlibat bi Ma’hadi Walisongo Cukir Jombang (Ilmu al-Lughah al-Ijtimai’y) - Imroaturrosyidah, Siti Nurfaizah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The phenomenon of code switching and code mixing often occurs among the community, including in the daily Arabic conversations of female students at the Putri Walisongo Islamic boarding school, the Syu'bah complex is an Arabic language complex at the Putri Walisongo Islamic boarding school which has Arabic language rules every day. In this case, researchers use qualitative research methods with tools to record and record the phenomena of code switching and code mixing that occur between female students at the Syu'bah Lughoh Arobiyyah complex. The results of this research are that the code switching phenomenon is divided into two, namely code switching into inner code mixing and code switching out of outer code mixing. Meanwhile, code mixing occurs between words, tarkib idhofi, repeated words, and clauses. Code switching and code mixing occur due to several factors, including students' lack of understanding of everyday vocabulary and a lack of desire to practice. So researchers want to improve the teaching system and practice of Arabic conversation so that they can speak Arabic fluently and correctly according to language rules.